Pendampingan Branding UMKM melalui Google Maps dan Banner untuk Peningkatan Pemasaran Lokal Desa Bakalan - Ibrahim Ibrahim; Mochammad Syafiuddin Shobirin; Sholechah Sholechah; Aulia Syafira Azzahro; Syaqila Maulidatina; Syahrul Rozaky (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to assist micro, small, and medium enterprises (MSMEs) in strengthening their business branding through the use of Google Maps and banners as local promotional media. The program was conducted in Bakalan Village, Sumobito District, Jombang Regency, involving two MSME partners, namely Rumah Laundry and Margo Roso Bakery. These two partners were selected because they had different needs in strengthening their business identity. Rumah Laundry did not yet have a clear visual identity and business profile, while Margo Roso Bakery already had a Google Maps account but still needed support in optimizing business information and strengthening offline branding. The program used a participatory approach through several stages, including field surveys, identification of partner needs, branding concept planning, assistance in managing business information, banner design and installation, Google Maps optimization, and evaluation. The results showed that this assistance helped the partners develop a clearer business identity, more attractive promotional media, and more accessible business information for the local community. The program also improved MSME owners’ understanding of the importance of consistent business identity in supporting local marketing. Therefore, branding assistance through Google Maps and banners can serve as a simple, practical, and relevant strategy to increase MSME visibility at the village level.